2005
DOI: 10.1111/j.1365-2443.2005.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐type 1 matrix metalloproteinase cytoplasmic tail binding protein‐1 (MTCBP‐1) acts as an eukaryotic aci‐reductone dioxygenase (ARD) in the methionine salvage pathway

Abstract: MTCBP-1 was identified as a protein that binds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…The coordinating amino acid residues seem to be well conserved also in eukaryotes (69). The MTA cycle reaction uses Fe 21 , whereas if Ni 21 is available 3-methylthiopropionate, formate, and carbon monoxide is formed instead, see Fig.…”
Section: Dioxygenasementioning
confidence: 99%
See 1 more Smart Citation
“…The coordinating amino acid residues seem to be well conserved also in eukaryotes (69). The MTA cycle reaction uses Fe 21 , whereas if Ni 21 is available 3-methylthiopropionate, formate, and carbon monoxide is formed instead, see Fig.…”
Section: Dioxygenasementioning
confidence: 99%
“…The dioxygenase in eukaryotes seems to be functionally conserved because the human dioxygenase could complement the corresponding yeast homologue (68,69) and, in Archaea, it seems that the dioxygenase is absent (31). In plants, the dioxygenase activity has been suggested to be regulated by combining the single polypeptide chains to oligomeric forms, which have a reduced catalytic activity (34).…”
Section: Dioxygenasementioning
confidence: 99%
“…Our analysis indicated that during infection P. brasiliensis seems to be able to synthesize asparagine, providing, in addition to glutamine, another site for transient storage of nitrogen. The novel transcript encoding aci-reductone dioxygenase suggests the presence of the methionine salvage pathway cycle (Hirano et al, 2005) providing additional methionine, which could be scarce in the host environment. Overall, the presumed increase in synthesis of the amino acids listed above implies that those compounds are not present at sufficient levels in host tissue to support growth of P. brasiliensis.…”
Section: Transcriptome Of P Brasiliensis During Infectionmentioning
confidence: 99%
“…Based on the evidence of XAS, site-directed mutagenesis and isothermal calorimetry experiments described in this paper as well as evidence from other laboratories and our own previous work (14,18), we conclude that the same amino acid residues, His 96, His 98, Glu 102 and His 140 provide the protein-based ligands for the metal in both Fe-and Ni-bound forms of ARD, and that both metals are bound in approximately octahedral geometry, with solvent-derived ligands providing the remainder of the coordination sphere. This conclusion implies that relatively subtle differences between the two metal-protein complexes are amplified by the surrounding protein structure, giving two enzymes of different structures and activities from a single polypeptide.…”
mentioning
confidence: 99%